Metabolic adverse events associated with systemic corticosteroid therapy—a systematic review and meta-analysis. Issue 12 (22nd December 2022) - Kulkarni, Spoorthy; Durham, Hannah; Glover, Luke; Ather, Osaid; Phillips, Veronica; Nemes, Szilard; Cousens, Leslie; Blomgran, Parmis; Ambery, Philip
Abstract : Objectives: To assess the risk of new-onset or worsening hyperglycaemia, hypertension, weight gain and hyperlipidaemia with systemic corticosteroid therapy (CST) as reported in published randomised control trial (RCT) studies. Data sources: Literature search using MEDLINE, EMBASE, Cochrane library, Web of Science and Scopus Study eligibility criteria: Published articles on results of RCT with a systemic CST arm with numerical data presented on adverse effect (AE). Participants and interventions: Reports of hyperglycaemia, hypertension, weight gain and hyperlipidaemia associated with systemic CST in patients or healthy volunteer's ≥17 years of age. Study appraisal methods: Risk of bias tool, assessment at the level of AE and key study characteristics. Results: A total of 5446 articles were screened to include 118 studies with 152 systemic CST arms (total participants=17 113 among which 8569 participants treated with CST). Pooled prevalence of hyperglycaemia in the CST arms within the studies was 10% (95% CI 7% to 14%), with the highest prevalence in respiratory illnesses at 22% (95% CI 9% to 35%). Pooled prevalence of severe hyperglycaemia, hypertension, weight gain and hyperlipidaemia within the corticosteroid arms was 5% (95% CI 2% to 9%), 6% (95% CI 4% to 8%), 13% (95% CI 8% to 18%), 8% (95% CI 4% to 17%), respectively. CST was significantly associated hyperglycaemia, hypertension and weight gain as noted in double-blinded placebo-controlled parallel-arms studies: OR of 2.13 (95% CI 1.66 to 2.72), 1.68 (95% CI 0.96 to 2.95) and 5.20 (95% CI 2.10 to 12.90), respectively. Intravenous therapy posed higher risk than oral therapy: OR of 2.39 (95% CI 1.16 to 4.91). Limitations: There was significant heterogeneity in the AE definitions and quality of AE reporting in the primary studies and patient populations in the studies. The impact of cumulative dose effect on incidental AE could not be calculated. Conclusions and implications of key findings: Systemic CST use is associated with increased risk of metabolic AEs, which differs for each disease group and route of administration. PROSPERO registration number: CRD42020161270.